An investigation of the determinants for community pharmacists' positive image and the needs for community pharmacists' services in Taiwan. (26th April 2019) - Tseng, Kuang‐hsun; Chang, Elizabeth H.; Ko, Yu
Summary: Objectives: To examine the specific factors that the general public believes have an effect on the image of community pharmacists and also to identify community pharmacists' services that truly fulfill people's needs. Methods: A convenient sample of 401 community pharmacy customers completed the questionnaire. Results: When asked about the factors that help establish a positive image for a community pharmacist, 98.3% of the respondents reported accurate dispensing as the most important factor, followed by cordial attitude (95.5%), and wearing clothes showing pharmacist's license with a photo (94.6%). Among the services provided by community pharmacies, most people think that the most needed service is a consultation explaining drug‐drug interactions (93.8%). Furthermore, 312 (77.8%) respondents indicated that there is a need for comprehensive pharmaceutical services. As for the amount that the respondents were willing to pay for such service, many (42.9%) chose 100 NT dollars (≈ 3USD). Conclusion: The results of this study showed that correct dispensing is the most important factor that helps establish a positive image of community pharmacists and that the most needed services were those that required pharmacists' professional competence. Moreover, nearly 80% of the respondents reported that they needed comprehensive pharmaceutical services and were willing to pay for it.